2008
DOI: 10.1111/j.1570-7458.2008.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungal loline alkaloids in grass–endophyte associations confer resistance to the rice leaf bug, Trigonotylus caelestialium

Abstract: Plant symbiotic fungi (endophytes) of the genus Neotyphodium [anamorphs, asexual derivatives of Epichloë (Ascomycota: Clavicipitaceae)] often associate with grass species of the subfamily Pooideae, which includes important forage and turf species. These endophytes are known to produce a range of alkaloids that enhance their host's resistance to insects or are toxic to grazing animals. Among the alkaloids, loline alkaloids (saturated 1-aminopyrrolizidines) are generally observed in the highest concentrations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…Some N. occultans-infected Italian ryegrass used in this study showed excellent resistance to T. caelestialium, similar to N. lolii-infected perennial ryegrass (Shiba & Sugawara, 2005) and N. uncinatum-infected meadow fescue (Shiba & Sugawara, 2009). The feeding preference and the survival rate of this insect were considerably lower on infected plants than on uninfected ones, and the higher the in planta N-formylloline concentration, the greater the adverse effects on the insect.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Some N. occultans-infected Italian ryegrass used in this study showed excellent resistance to T. caelestialium, similar to N. lolii-infected perennial ryegrass (Shiba & Sugawara, 2005) and N. uncinatum-infected meadow fescue (Shiba & Sugawara, 2009). The feeding preference and the survival rate of this insect were considerably lower on infected plants than on uninfected ones, and the higher the in planta N-formylloline concentration, the greater the adverse effects on the insect.…”
Section: Discussionsupporting
confidence: 54%
“…This hypothesis is derived from the toxic effect of the chemical to the insect as indicated by the force feeding of the purified chemical performed in Shiba & Sugawara (2009). Significant correlation between N-formylloline concentration in plants and the survival of the insects was observed when they were reared on the inflorescences of N. occultans-infected Italian ryegrass. These results indicate that N. occultans-infected Italian ryegrass deterred feeding of T. caelestialium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The survival of S. rubrovittatus fed on the N ‐formylloline was investigated using a membrane‐feeding assay as described previously (Shiba and Sugawara ). Purified N ‐formylloline (extracted and purified from endophyte‐infected meadow fescue [ Festuca pratensis Huds.…”
Section: Methodsmentioning
confidence: 99%
“…(). The Epichloë ‐produced alkaloid, N ‐formylloline, has been shown to confer resistance to this insect species on the host grasses, concentration dependently (Shiba and Sugawara ; Shiba et al . ).…”
Section: Introductionmentioning
confidence: 99%